Dreams, Dreamers, and Visions : The Early Modern Atlantic World - Tuttle, Leslie, 1967-; Plane, Ann Marie, 1964- (Book collections on Project MUSE., 2013)
In this volume, scholars from three continents trace the role of dreams in the cultural transitions of the early modern Atlantic world, illustrating how both indigenous and European methods of understanding dream phenomena became central to contests over religious and political power.